The Forgotten Library of the Botanist Friedrich Welwitsch (1806-1872) - Albuquerque, Sara (2021)
The National Museum of Natural History and Science (MUHNAC/Museums of the University of Lisbon, Portugal) houses a forgotten treasure: part of the scientific and working library of the Austrian botanist Friedrich Martin Joseph Welwitsch (1806-1872), known worldwide for his work on Angolan flora. The museum’s collections began to be reorganized in 2012, enabling the library to be re-assembled, and 198 volumes were found. Although a great deal has already been written on the Austrian botanist, this paper seeks to explore the international scientific network to which he belonged, based on an analysis of his private library, correspondence, and working notes.